PERBAIKAN TATA LETAK GUDANG DAN SISTEM MANAJEMEN GUDANG DI BONCHEL PETSHOP SURABAYA - Muhammad Yoga Putra Indarto; Stefanus Soegiharto; Dina Natalia Prayogo (CALYPTRA, 2023)
Abstract — Bonchel Petshop is a company engaged in the sale of pet supplies from food, snacks, medicine, cages to accessories. In the Bonchel Petshop business, it does not only sell pet equipment, but also has grooming and lodging and mating services, especially for cats. The layout of the Bonchel Petshop warehouse is still messy because incoming goods from suppliers to the warehouse are still randomly placed in the warehouse. The location for the placement of incoming goods is not placed according to the category. This probl em makes the time for taking orders by warehouse staff to be ineffective and ineffective. Data collection for this study was carried out by conducting interviews and historical data from the Bonchel Petshop warehouse. The method used in placing goods on shelves uses the classed-based storage method in which goods are placed according to the category of goods. The purpose of using this method is to increase the effectiveness and efficiency of time in searching for goods by warehouse staff. Data processing is done by ABC analysis to determine the level of frequency of incoming and outgoing goods to the warehouse. Category A ranking has a frequency requirement of 80% for the frequency of goods taking, B-rank category has a 15% proportion requirement and C ranking category has a 5% percentage requirement for goods in and out. Category ranking A is obtained by a wide rack of 26 m2. Rank B has a shelf area of 6 m2 and category C rank has a shelf area of 4 m2. From the results of these calculations, Bonchel Petshop requires adding shelves to 8 racks and 5 pallets to store products in the warehouse based on warehouse stock data for 6 months. Adding shelves and reducing pallets results in the aisle on the 1st floor being 29.6 m2 and the 2nd floor being 25.35 m2. Data collection was carried out by observing for three days at the Bonchel Petshop and obtaining an average proportion of search time savings in the tourist layout design of 25% from the initial layout. Keywords: warehouse layout, abc analysis Abstrak—Bonchel Petshop merupakan perusahaan yang bergerak dalam bidang penjualan perlengkapan hewan peliharaan dari makanan, snack, obat, kandang hingga aksesoris. Dalam bisnis Bonchel Petshop tidak hanya menjual perlengkapan hewan peliharaan namun memiliki jasa grooming dan tempat penginapan maupun kawin khususnya untuk kucing. Tata letak gudang Bonchel Petshop masih berantakan dikarenakan penempatan barang masuk dari supplier ke gudang masih ditempatkan secara acak di gudang. Lokasi penempatan barang yang masuk tidak ditempatkan sesuai kategori. Masalah tersebut membuat waktu picking order oleh staf gudang menjadi tidak efesien dan efektif. Pengumpulan data untuk penelitian ini dilakukan dengan melakukan wawancara dan data histor y dari gudang Bonchel Petshop. Metode yang digunakan dalam penempatan barang di rak menggunakan metode classed-based storage yang mana barang diletakkan sesuai dengan kategori barang. Tujuan penggunaan metode tersebut untuk meningkatkan efektivitas dan efisiensi waktu dalam pencarian barang oleh staf gudang. Pengolahan data dilakukan dengan analisis ABC untuk mengetahui tingkat frekuensi keluar masuk barang ke gudang. Kategori ranking A memiliki ketentuan presentase frekuensi pengambilan barang sebesar 80%, kategori ranking B memiliki ketentuan persentase sebesar 15 % dan untuk kategori ranking C memiliki ketentuan presentase frekuensi keluar masuk barang sebesar 5%. Kategori ranking A didapatkan luas rak sebesar 26 m2. Ranking B memiliki luas rak sebesar 6 m 2 dan kategori ranking C didapatkan luas rak sebesar 4 m2. Dari hasil perhitungan tersebut Bonchel Petshop membutuhkan penambahan rak menjadi 8 rak dan 5 pallet untuk menyimpan produk yang ada di gudang berdasarkan data stok gudang selama 6 bulan. Adanya penambahan rak dan pengurangan pallet maka di dapatkan aisle lantai 1 menjadi 29,6 m2 dan lantai 2 menjadi 25,35 m2. Pengambilan data dilakukan dengan cara melakukan pengamatan selama tiga hari di Bonchel Petshop dan mendapatkan persentase rata -rata penghematan waktu pencarian pada rancangan layout usulan sebesar 25% dari layout awal. Kata kunci: tata letak, analisis abc